2013
DOI: 10.1097/prs.0b013e31829586c1
|View full text |Cite
|
Sign up to set email alerts
|

A Nationwide Analysis of the Relationship between Hospital Volume and Outcome for Autologous Breast Reconstruction

Abstract: Risk, III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 35 publications
2
42
0
1
Order By: Relevance
“…[31][32][33][34][35][36][37] One study has examined the effect of surgeon-surgeon familiarity on implant-based breast reconstruction and concluded that complication rates are not affected by surgeon familiarity. 38 However, this study had low statistical power, considering the number of patients (n = 511) who were analyzed, for us to evaluate nine surgical teams.…”
Section: Discussionmentioning
confidence: 98%
“…[31][32][33][34][35][36][37] One study has examined the effect of surgeon-surgeon familiarity on implant-based breast reconstruction and concluded that complication rates are not affected by surgeon familiarity. 38 However, this study had low statistical power, considering the number of patients (n = 511) who were analyzed, for us to evaluate nine surgical teams.…”
Section: Discussionmentioning
confidence: 98%
“…17 For example, high-volume centers are associated with lower complication rates but are often located in metropolitan centers, resulting in increased travel distance for patients residing in rural areas. 15,18 Greater travel distance creates both direct (e.g., commute cost) and indirect (e.g., time, foregone wages) economic barriers, thereby restricting health care options for many patients. 19 The premise of the current report was to use travel distance as a proxy for measuring the influence of geographic barriers on breast reconstruction rates and methods.…”
Section: Discussionmentioning
confidence: 99%
“…15 These trends were analyzed with Poisson regression. All statistical analyses were performed using Stata 11.0 (StataCorp, College Station, Texas).…”
Section: Methodsmentioning
confidence: 99%
“…These databases have been used to explore practice patterns, healthcare utilization, and access to care for many plastic surgery-related procedures and diagnoses. For example, using the NIS database, Albornoz et al 13 found that higher-volume autologous breast reconstruction centers had lower complication rates than lower volume centers. Squiteri et al 14 found racial and insurancebased disparities in pediatric replantation rates using the KID database.…”
Section: Healthcare Cost and Utilization Projectmentioning
confidence: 98%
“…Data not available to nonaccredited facilities. 13 To participate, they must be members of Children's Hospital Association. Children's Hospital Association membership and Pediatric Health Information System access require separate, annual fees.…”
Section: Attributes Of Large Administrative Databasesmentioning
confidence: 99%